Relationship between obesity and osteoporosis in postmenopausal women at the Arzobispo Loayza National Hospital - Hinojosa Andía, Lucy J. (2024)
Introduction: osteoporosis is one of the most prevalent metabolic bone diseases; it is chronic in evolution and produces significant morbidity and mortality in the elderly. This disease is altered by multiple factors; one of them is obesity, which seems to act as a protecting factor and, due to its epidemic nature, may be important.Objectives: previous research in developed countries has shown obesity to be a protective factor against osteoporosis, but there is no current specific investigation addressing this possibility in Peruvian women. This study seeks to explore this relationship in postmenopausal women who attended the rheumatology service of the Arzobispo Loayza National Hospital (Lima, Perú) between 1997 and 2000.Material and methods: the design used was a paired case and control study, with incidentall sampling to saturation. Cases were defined as patients with a clear diagnosis of osteoporosis by lumbar spine densitometry,carried out with the DEXA technique.Controls were patients equivalent in age, time of menopause and number of children, who were not osteoporotic.Results: 1 738 patients met selection criteria; 227 case and control pairs were formed, with perfect matching. Frequency of obesity in the control group was 27.8%, and in the case group was 20,7%. An odds ratio of 0.67 was obtained, with a 95% confidence interval 0.424-1.07 (p value = 0.098).Conclusions: this study did not reveal a statistically significant relationshipbetween obesity and osteoporosis. A protective effect between those variables seems to exist, and it will have to be investigated further.